Aplikasi E-voting Berbasis Blockchain dengan Metode Smart Contract - Junaedi, Junaedi; Fernando, Albert; Hermawan, Aditiya (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2024)
Voting is an important process in many contexts, such as in organizational decisions and the selection of leaders. With the development of technology, the concept of electronic voting emerged, where humans can cast their votes electronically. Electronic voting has become an important alternative in organizational decision making and leader selection, but often faces challenges related to security and fraud. In this study, a blockchain-based electronic voting application has been developed using the Smart Contract method. Blockchain technology was chosen because of its decentralized and public nature, which can provide a high level of security and transparency to voting data. Evaluation of the application was carried out through a questionnaire filled out by 39 respondents. The results showed a high level of agreement, with 91.46% of respondents stating that they strongly agreed with the effectiveness of this application. This indicates that the implementation of a blockchain-based electronic voting system has the potential to increase trust and integrity in the election process. In addition, this application also offers easy access and data transparency, which is expected to increase public participation in the democratic process. By continuing to conduct further research and development, this blockchain-based electronic voting application has great potential to become the standard in future elections.